Peningkatan Kesejahteraan Masyarakat Desa Antajaya, Kecamatan Tanjungsari, Kabupaten Bogor melalui Penguatan BumDes - Supriadi Thalib; Ati Hermawati; Tia Ichwani (FEB-UP Press, 2020)
Community Service Activities aim to improve the welfare of the people of Antajaya Village, Tanjung Sari District, Bogor Regency through strengthening the BUMDes, with a three-year Sustainable Program. Methods of implementing Community Service Dissemination and mapping on village community participation in BUMDes, and the quality of BUMDes management. The community participating in this activity is expected to be able to understand the role and function of BUMDes which has great benefits for the welfare of the village community, and for BUMDes able and weakness of BUMDes to be able to take the opportunity and face the threats that exist. The results of the socialization and mapping of these activities were obtained by the Village Communities to understand the importance of BUMDes for their welfare, so the Village Communities were strongly motivated to participate in economic transactions with the BUMDes, while the BUMDes were committed to collaborating with the Higher Education in this case the Faculty of Economics and Business of the Pancasila University in a sustainable manner. to attend training, mentoring and business consultation to improve BUMDes Performance, because there are a lot of potential village resources that have not been optimized to produce Value Added products from BUMDes, meaning that many opportunities can be taken to produce superior products in the village.